Meningkatkan Prestasi Belajar PPKn Kompetensi Dasar Hak dan Kewajiban Terhadap Lingkungan Melalui Model Pembelajaran Problem Based Learning Siswa Kelas IV SDIT Mutiara Hati Ngargoyoso Tahun Pelajaran 2021/2022 - Agus Tugiyanto; Anita Trisiana; siti Supeni (Prodi PPkn Universitas Slamet Riyadi, 2023)
The Purpose of this was to identify procedures and way to apply the problem based learning (PBL) model that could improve student achievement in class IV SDIT Mutiara Hati Ngargoyoso. Thys type research is Classroom Action Research (CAR). The research subjects were students in grade IV SDIT Mutiara Hati Ngargoyoso in the 2021/2022 academic year a total of 27 students. This research was conducted in two cycles. Each cycle cinsisted of four stages such a planning, implementing, observing, and reflecting. The research subjects were selected based on the result of the first semester test score. The result showed that class IV had a low-class average and mastery grade. Data collection technique used was descriptive which compared the test score in the first cycle with the test score in the second cycle. The success criterion for learning outcomes was the minimum score of 75 (KKM = 75) and minimum score of class was 85%. The result showed that there was an improvement in Civics learning outcomes in the initial conditions (initil ability test), cycle 1 and cycle II. On theinital ability test, the average value was only 77,44. In cycle 1, the average value has increased. The result was that the average score was 79,22 and students who got scores ≥ 75 are 24 students. Furthermore, in cycle II also experienced an increase. The result is that the average value became 85,11 and minimum score of class became 100%. Student who score ≥ 75 were 27 students. Based on the results, it could be concluded that the implementation of the problem-based learninng (PBL)model can improve student achievement in class IV SDIT Mutiara Hati Ngargoyoso. Keyword : Problem Based Learning (PBL) Model, Learning Achievement, Rights and Obligations